Development of Couette-Taylor Crystallizer in Cooling Crystallization: Promotion of Size Distribution of L-lysine - Trinh, Huyen Thi Thanh; Nguyen, Tuan Anh; Phan, Thao Thanh; Khuu, Quang Chau; Dang, Giang Truong (Vietnam Journal of Science and Technology, 2016)
The Couette-Taylor (CT) crystallizer was developed to promote the size distribution of L-Lysine crystal product in cooling crystallization. When using the CT crystallizer, the size distribution of crystal product was much narrower than that of the conventional Stirred tank (ST) crystallizer. Here, the coefficient size distribution (n) in CT crystallizer was quite large as 3.43, while it was only 2.17 in ST crystallizer at the same 360 rpm of agitation or rotation speed. This result indicated that the CT crystallizer was much more effective than the ST crystallizer in terms of the size distribution of L-lysine crystal products in cooling crystallization. The advantage of CT crystallizer over the ST crystallizer was explained in terms of the high energy dissipation of Taylor vortices flow, where it was 7.6 times higher than that of random fluid motion in conventional ST crystallizer. As such, the supersaturation profile in the CT crystallizer was much more homogeneous than that in the ST crystallizer, which resulted in promotion of size distribution L-lysine crystal product.